Cold lumbar abscesses due to tuberculous spondylitis - V Haydan; L Médart (Journal of the Belgian Society of Radiology, 2013)
A 33-year-old man, originating from Morocco, came to the hospital with a one-month history of right paralumbar mass. His general condition was good except for some weight loss. He had no fever. Blood tests showed a moderate inflammatory syndrome.